2013
DOI: 10.7196/samj.6159
|View full text |Cite
|
Sign up to set email alerts
|

Gastric adenocarcinoma in Zambia: A case-control study of HIV, lifestyle risk factors, and biomarkers of pathogenesis

Abstract: Background Gastric cancer is a leading cause of cancer deaths worldwide but there are few data from Africa. We have recently observed a trend towards diagnosis in younger patients. Objective To test the hypothesis that HIV may have altered risk factors for acquisition of gastric cancer, in a case-control study in the University Teaching Hospital, Lusaka, Zambia. Methods Cases (n=52) with confirmed gastric adenocarcinoma and controls (n=94) undergoing endoscopy but with no macroscopic gastric pathology. Est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 20 publications
2
27
2
1
Order By: Relevance
“…This is the first study that prospectively collected data on the age distribution of esophageal cancer patients in Zambia, and we have found that 28% were below the age of 45 years. This is similar to our previous findings in gastric cancer cases in which 21% were below 45 years 36 , and an earlier retrospective report on esophageal cancer in which it was 27% 7 . Taken together, these data from one central, busy endoscopy unit indicate that there is an emerging problem with gastrointestinal cancers in young Zambian adults.…”
Section: Discussionsupporting
confidence: 92%
“…This is the first study that prospectively collected data on the age distribution of esophageal cancer patients in Zambia, and we have found that 28% were below the age of 45 years. This is similar to our previous findings in gastric cancer cases in which 21% were below 45 years 36 , and an earlier retrospective report on esophageal cancer in which it was 27% 7 . Taken together, these data from one central, busy endoscopy unit indicate that there is an emerging problem with gastrointestinal cancers in young Zambian adults.…”
Section: Discussionsupporting
confidence: 92%
“…Neither the aetiology nor the consequence of this finding is clear. In addition, HIV infection was not found to be associated with gastric cancer [9]. In this study, we found no correlation between HIV infection and gastric atrophy, suggesting that the hypochlorhydria seen in HIV infection cannot be explained by the loss of normal gastric mucosa cells.…”
Section: Discussioncontrasting
confidence: 63%
“…Although this might have allowed secular changes to alter the HEV transmission profile in this community, we have seen no evidence of major changes in drinking water or sanitation, and the Helicobacter pylori seroprevalence in adults has remained absolutely constant at 81% [19, 20]. …”
Section: Discussionmentioning
confidence: 99%